Pengenalan Alat Pengering Energi Surya Serbaguna Untuk Pengeringan Pakaian dan Herbal di Madrasah Aliyah Mambaul ‘Ulum Kabupaten Bengkulu Tengah - Yuwana, Yuwana; Marsigit, Wuri; Hidayat, Lukman (DHARMA RAFLESIA, 2022)
The difficulty faced by the target group of Madrasah Aliyah Mambaul Ulum in drying clothes, and herbs needed to be solved. This community service activity aimed to adopt a multi-purpose solar dryer to solve this problem. The activities consisted of counseling, manufacturing, and testing the dryer, demonstration of the clothes and herb dryings, herb packaging and utilization, and assistance on the use of dryer by the target group to dry cloths and herbs independently. The counseling activities were delivered by the community service team (students and lecturers) to the target group consisting of a class of selected students along with the Madrasah Principal and 3 teachers. The manufacture and operation testing were carried out by a mechanic and students under the supervision of lecturers. The demonstration of drying was carried out by students and the target group. The dryer was then operated to dry cloth by the target group. Packaging and serving of dried herbs were practiced by students and the target group. Assistance in the utilization of the dryer to dry clothes and herbs independently was carried out by students under the supervision of the lecturers. All the community service activities were completed. It is suggested that the introduced appropriate technology may be adapted to wider target groups.